FGL1 as a modulator of plasma D‐dimer levels: Exome‐wide marker analysis of plasma tPA, PAI‐1, and D‐dimer. (30th May 2021) - Thibord, Florian; Song, Ci; Pattee, Jack; Rodriguez, Benjamin A.T.; Chen, Ming‐Huei; O'Donnell, Christopher J.; Kleber, Marcus E.; Delgado, Graciela E.; Guo, Xiuqing; Yao, Jie; Taylor, Kent D.; Ozel, Ayse Bilge; et al.
Abstract: Background: Use of targeted exome‐arrays with common, rare variants and functionally enriched variation has led to discovery of new genes contributing to population variation in risk factors. Plasminogen activator‐inhibitor 1 (PAI‐1), tissue plasminogen activator (tPA), and the plasma product D‐dimer are important components of the fibrinolytic system. There have been few large‐scale genome‐wide or exome‐wide studies of PAI‐1, tPA, and D‐dimer. Objectives: We sought to discover new genetic loci contributing to variation in these traits using an exome‐array approach. Methods: Cohort‐level analyses and fixed effects meta‐analyses of PAI‐1 ( n  = 15 603), tPA ( n  = 6876, ) and D‐dimer ( n  = 19 306) from 12 cohorts of European ancestry with diverse study design were conducted, including single‐variant analyses and gene‐based burden testing. Results: Five variants located in NME7, FGL1, and the fibrinogen locus, all associated with D‐dimer levels, achieved genome‐wide significance ( P  < 5 × 10 −8 ). Replication was sought for these 5 variants, as well as 45 well‐imputed variants with P  < 1 × 10 −4 in the discovery using an independent cohort. Replication was observed for three out of the five significant associations, including a novel and uncommon (0.013 allele frequency) coding variant p.Trp256Leu in FGL1 (fibrinogen‐like‐1) with increased plasma D‐dimer levels. Additionally, a candidate‐gene approach revealed a suggestive association for a coding variant (rs143202684‐C) in SERPINB2, and suggestive associations with consistent effect in the replication analysis include an intronic variant (rs11057830‐A) in SCARB1 associated with increased D‐dimer levels. Conclusion: This work provides new evidence for a role of FGL1 in hemostasis.